Inhibition of Stat3 Signaling Pathway by Natural Product Pectolinarigenin Attenuates Breast Cancer Metastasis - Li, Yali; Gan, Cailing; Zhang, Yange; Yu, Yan; Fan, Chen; Deng, Yuanle; Zhang, Qianyu; Yu, Xi; Zhang, Yiwen; Wang, Liqun; He, Fang; Xie, Yongmei; et al. (Frontiers in Pharmacology, 2019)
Background: Breast cancer is the most common female cancer with considerable metastatic potential, which urges the need for developing novel potential drug candidate to inhibit tumor metastasis. Signal transducer and activator of transcription 3 (Stat3) has critical roles in cancer growth and metastasis and has been confirmed as a promising anticancer target. Here, we report our finding with pectolinarigenin, a flavonoids compound isolated from the aerial parts of C. chanroenicm. Methods: The role of Pec. in cell proliferation, cell apoptosis and cell migration and invasion in three breast cancer cells (4T1, MDA-MB-231, MCF-7) was investigated. Cell proliferation was determined by MTT assay; cell apoptosis was determined by Flow cytometry; protein expression was detected by western blotting. Tumor xenograft mice model and breast tumor metastasis model in vivo were built to further assess the effects of Pec. on 4T1 cells. Results: Intraperitoneal administrations of pectolinarigenin significantly inhibited breast cancer metastasis to lungs without affecting the tumor growth of incubated 4T1 breast cancer cells. Pectolinarigenin could also recruit CD8+ T cells to mediate tumor immune response. Furthermore, pectolinarigenin markedly impaired cancer cell migration and invasion by down-regulating phosphorylated-Stat3, and expression of matrix metalloproteinase (MMP)-2, MMP-9, while up-regulating the expression of TIMP2. We also found that pectolinarigenin inhibited breast cancer cell proliferation and induced apoptosis via mitochondrial-related apoptosis pathway, reduced mitochondrial membrane potential and the expression of Bcl-2, increasd expression of Bax and cleaved caspase-3 as well as disturbed the ROS generation. Conclusions: Pectolinarigenin might potentially be a candidate for metastasis of breast cancer by mediating Stat3 pathway.